East Industrial Pedestrian Bridge: A Case Study of Value Engineering and High Performance Material - Tzaveas, Theodoros (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
East Industrial Road, a main arterial for the city of Doha with high average daily traffic, made crossing by foot being not only challenging, but also dangerous. Authorities proposed to build a pedestrian bridge over East Industrial Road which would allow for easy, safe travel over this busy roadway. As part of initiatives towards reduced cost of road construction and maintenance, alternative materials for the bridge were considered. For the construction phase, quick installation and utilization of prefabricated units, and for the operational phase, solutions not requiring periodical maintenance were favored. The primary objective of this paper is to describe the potential of aluminum in competition with common steel solutions for this pedestrian bridge. Collaborative design work remains a key aspect in projects that addresses not only technical efficiency but also human experience. Cross-disciplinary collaboration requires a language that allows exchanges across disciplinary boundaries. This paper also discusses the design process of the first pedestrian bridge built in Qatar made of structural aluminum. As engineering and building challenges increase in complexity due to environmental and political factors inherent in the modern age, as well as ever accelerating changes in technology, project clients are seeking ways for effective management. The purpose of value engineering is to improve the value of the project designs and to demonstrate to the client that the objective of value has been achieved. The process is documented to illustrate the range of considerations required in the design/construction team to ensure a successful project implementation.